2011
DOI: 10.1016/j.foodcont.2011.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation applied to studying continuous spirit distillation and product quality control

Abstract: a b s t r a c tThis work aims to study continuous spirit distillation by computational simulation, presenting some strategies of process control to regulate the volatile content. The commercial simulator Aspen (Plus and dynamics) was selected. A standard solution containing ethanol, water and 10 minor components represented the wine to be distilled. A careful investigation of the vaporeliquid equilibrium was performed for the simulation of two different industrial plants. The simulation procedure was validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…In parallel to this experimental approach, many researchers have used simulation to explore the behaviour of the volatile compounds and the influence of the operating parameters on distillation. Many studies have been published on continuous distillation in multistage columns , batch distillation in columns or alembic . For batch distillation in alembic stills, Scanavini et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel to this experimental approach, many researchers have used simulation to explore the behaviour of the volatile compounds and the influence of the operating parameters on distillation. Many studies have been published on continuous distillation in multistage columns , batch distillation in columns or alembic . For batch distillation in alembic stills, Scanavini et al .…”
Section: Introductionmentioning
confidence: 99%
“… carried out a bibliographic review, gathering all available data on liquid–vapour equilibria for volatile compounds in hydro‐alcoholic solutions, covering 44 volatile compounds belonging to several chemical families (12 alcohols, 12 esters, nine carboxylic acids, one acetal, seven carbonyl compounds, one furan and two terpenes). The ‘Non Random Two Liquids’ (NRTL) model was selected to represent the non‐ideality of the solution , as advised by Batista and Meirelles and Valderrama et al . .…”
Section: Introductionmentioning
confidence: 99%
“…The Lancet (The Lancet, 1901) reported: "It has intoxicating and poisonous properties superior to those of ordinary spirits, and is said to be known in some of the northern counties of Europe to the consumers of corn brandy who frequently ask to be served with a 'glass of good fusel'." The compounds 3-methyl-1-butanol, butan-1-ol, propan-1-ol and propan-2-ol are primarily responsible for the aroma of distilled spirits (Batista and Meirelles, 2011;Scanavini et al, 2012), but high concentrations of these compounds can cause health problems (Opdyke, 1978;Lachenmeier et al, 2008).…”
Section: Fusel Oil Removal In Beveragesmentioning
confidence: 99%
“…Two to 6.5% of the total feed ethanol must be purged to remove fusel oil from the distillate (neutral distillate) (Valderrama et al, 2012). Batista and Meirelles (2011) reported that, in the distillation of drinking ethanol, the higher alcohols become more concentrated in the distillate at low distillate flow rates and low reflux ratios. The equilibrium curve of the ethanol/water/3-methyl-1-butanol system at a temperature of 25 °C shows that there is a wide concentration range over which two phases co-exist in the system, which can be used to separate and remove 3-methyl-1-butanol (Kadir et al 2008).…”
Section: Fusel Oil Removal In Beveragesmentioning
confidence: 99%
See 1 more Smart Citation